Perceived Roles of Primary Health Care Services in the Prevention and Control of Cholera among Bwari Residents, Abuja - AJAYI, Ayodotun Edward; ALIYU, Tukur; FADERO, Oluwakemi Florence; MAZADU, Liti; ADEBAYO, Isaac Olalekan; SANI, Mohammed Ahmed (Ilorin Journal of Education, 2025)
The objectives were to assess whether (i) Health Education (ii) supply of essential drugs (iii) Prevention and control of endemic diseases are perceived roles of Primary Health Care Services in the prevention and control of cholera among Bwari residents, Abuja. The research design adopted for the study was a descriptive research design of the survey type. 454 respondents were sampled for the study among Bwari Residents. Inferential Statistics of one one-sample t-test at 0.05 significance level was used to test the three research null hypotheses set for the study. The findings of the study revealed that: Health education is a role of Primary Health Care Services in the prevention and control of cholera among Bwari residents, Abuja. because cal. t-val. (27.80) exceeds the crit. t-val. of 1.960 at df (454). Essential drug is role of Primary Health Care Services in the prevention and control of cholera among Bwari residents, Abuja, because the cal. t-val. (21.33) exceeds the crit. t-val. of 1.960 at df (454) Prevention and control of endemic and epidemic diseases is the role of Primary Health Care Services in the prevention and control of cholera among Bwari residents, Abuja, because the cal. t-val. (19.32) exceeds the crit. t-val. of 1.960 at df (454). This study concluded that health education, supply of essential drugs, and prevention and control of endemic and epidemic diseases are roles of Primary Health Care Services. It was recommended that the government should intensify efforts in community health education, regular and sufficient supply of essential drugs to manage cholera, and prevention of cholera through health promotional activities.